2009
DOI: 10.1007/s11655-009-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation on the treatment of post-cesarean hypogalactia by auricular points sticking-pressing

Abstract: APSP shows an apparent efficacy in treating PCH and is worthy of application in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
1
3
0
10
Order By: Relevance
“…Other studies have shown similar effects, though the site of massage/acupressure was different [12,13]. The mean number per day of urination and stools passed by the babies were higher in study group.…”
Section: Discussionsupporting
confidence: 60%
“…Other studies have shown similar effects, though the site of massage/acupressure was different [12,13]. The mean number per day of urination and stools passed by the babies were higher in study group.…”
Section: Discussionsupporting
confidence: 60%
“…Na Inglaterra, foi comprovada a produção da galactorreia a partir da acupuntura e evidenciada a produção da ocitocina e prolactina (15) . Um estudo randomizado, realizado em tal lugar, também chegou aos resultados positivos da melhora da hopogalactia a partir da auriculoterapia (16) . Em pesquisa realizada por Yu Zhou, com grupo controle em mulheres em poucos momentos antes do parto, foi realizado a auriculoterapia, assim, chegou-se à conclusão de que a auriculoterapia pode ser o método mais eficaz para a promoção do aleitamento materno em puérperas (17) .…”
Section: Resultsunclassified
“…Acupoint massage adalah teknik relaksasi, dan mengurangi stres yang bertanggungjawab atas peningkatan produksi susu (Patel, 2013). Acupoint massage pada titik-titik auricular efektif pada produksi air susu ibu yaitu pada titik AH10, CO18, CO13, CO12, dan CO4 (Zhou et al, 2009;Esfahani, et al, 2015;Lee, 2004;Widyawati, 2017). Akupresur yang umum digunakan dalam bidang kebidanan mengunakan tangan untuk menekan beberapa titik akupunktur pada tubuh.…”
Section: Pendahuluanunclassified